Training English for Educator at SMP Angkasa, Tuban – Kuta, Bali - Widiadnya Putri, I Gusti Ayu Vina; Santika, I Dewa Ayu Devi Maharani (Universitas Pendidikan Ganesha, 2020)
This program aims to give English training to Educator at SMP Angkasa, Tuban-Kuta, Bali. In general, the priority problems faced by educators in SMP Angkasa are the low quality of spoken and written English communication in understanding English vocabulary which is often used in the learning process. This is due to a lack of mastery of English vocabulary, lack of understanding of English theory, and lack of motivation to improve their English language skills. Besides that, most of the educators at SMP Angkasa are educators from various disciplines, so mastering English for them is not a priority.Â The training is focused on providing material on how to communicate well in transferring learning materials to students by communicating in English. Enrich the vocabulary that is often used by educators in the implementation of the teaching and learning process. This community service activities uses methods in the form of application of science and technology with an orientation towards providing English language training and training in communication skills through lectures, demonstrations, and questions and answers. From the English training given to educators at SMP Angkasa, it can be seen that the progressive progress of the trainees towards the use of English for oral and written communication. The progress in communication is evidenced by the use of English when delivering material in class. Furthermore, the ability to listen to the simple spoken conversations of the trainees has also increased, which can be seen during the training. Teachers use full English as the language of instruction during training and trainees can carry out the instructions given at that time well. Finally, there is progress in the ability to read and write simple information from the trainees. This is evidenced by the teaching material prepared by the training participants which is compiled in English and then discussed with the students in their respective classes also in the language of instruction is English.